Combined role of SiC particles and SiC whiskers on the characteristics of spark plasma sintered ZrB2 ceramics. Issue 5 (1st April 2020) - Pazhouhanfar, Yaghoub; Sabahi Namini, Abbas; Shaddel, Shahrzad; Ahmadi, Zohre; Shahedi Asl, Mehdi
Abstract: In this research work, the effects of silicon carbide (SiC) as the most important reinforcement phase on the densification percentage and mechanical characteristics of zirconium diboride (ZrB2 )-matrix composites were studied. In this way, a monolithic ZrB2 ceramic (as the baseline) and three ZrB2 matrix specimens each of which contains 25 vol% SiC as reinforcement in various morphologies (SiC particulates, SiC whiskers, and a mixture of SiC particulates/SiC whiskers), have been processed through spark plasma sintering (SPS) technology. The sintering parameters were 1900 °C as sintering temperature, 7 min as the dwell time, and 40 MPa as external pressure in vacuum conditions. After spark plasma sintering, a relative density of 96% was obtained (using the Archimedes principles and mixture rule for evaluation of relative density) for the unreinforced ZrB2 specimen, but the porosity of composites containing SiC approached zero. Also, the assessment of sintered materials mechanical properties has shown that the existence of silicon carbide in ZrB2 matrix ceramics results in fracture toughness and microhardness improvement, compared to those measured for the monolithic one. The simultaneous addition of silicon carbide particulates (SiCp ) and whiskers (SiCw ) showed a synergistic effect on the enhancement of mechanical performance of ZrB2 -based composites.